Determination of Chlorinated Paraffins (CPs) in Human Blood Serum of Czech Population - Tomasko, Jakub; Stupak, Michal; Parizkova, Denisa; Polachova, Andrea; Sram , Radim J.; Topinka, Jan; Pulkrabova , Jana (Cutting Edge Research in Biology Vol. 3, 2023)
This study aimed to validate a previously published [1] method for the simultaneous determination of PCBs, PBDEs, OCPs and novel FRs for additional analysis of SCCPs and MCCPs in human blood serum. For CPs determination, gas chromatography coupled with high resolution mass spectrometry in negative chemical ionisation mode (GC-NCI-HRMS) was employed instead of gas chromatography coupled with tandem mass spectrometry applied for the analysis of other halogenated contaminants. The environmental pollutants known as short- and medium-chain chlorinated paraffins (SCCPs; MCCPs) are pervasive, have the ability to bioaccumulate, and have a negative impact on human health. Assessment of human exposure to various contaminants, such as SCCPs and MCCPs, includes the analysis of blood serum. Lately, the information about the exposure of Chinese population has been reported; nevertheless, data on human exposure to SCCPs and MCCPs outside East Asia are still very limited. In this pilot study, SCCPs and MCCPs were determined in 27 serum samples obtained from Czech adults. The samples were extracted by a three-step extraction (repeated with a clean solvent) by a mixture of n-hexane:diethyl ether (9:1, v/v) with subsequent clean-up on Florisil® solid phase extraction column. Gas chromatography coupled with high resolution mass spectrometry operated in negative chemical ionisation was employed for the instrumental analysis. The method recoveries ranged from 71 to 89% with repeatabilities of <20% (expressed as relative standard deviation). In the samples, SCCP concentrations were in the range of <150–2600 ng/g lipid weight, lw (median 370 ng/g lw) and the MCCP concentrations were in the range of <200–2110 ng/g lw (median 360 ng/g lw), respectively. To the best of our knowledge, the data we have published about chlorinated paraffins in human blood serum in Europe is the first evidence of exposure to these chemicals and their potentially harmful effects on human health.